PENGARUH PENGETAHUAN DAN SIKAP TENTANG RESIKO BENCANA BANJIR TERHADAP KESIAPSIAGAAN REMAJA USIA 15 â 18 TAHUN DALAM MENGHADAPI BENCANA BANJIR DI KELURAHAN PEDURUNGAN KIDUL KOTA SEMARANG - Purwoko, Alif; Sunarko, Sunarko; Putro, Saptono (Jurnal Geografi, 2015)
The role of a teenager when flood is emergency response, teenagers are always involved in saving both livesand property. This study aims to determine the level of knowledge of adolescents 15-18 years about floods,and to discover the influence of knowledge on the preparedness of adolescents 15-18 years toward floods.The research was conducted in the Village Pedurungan Kidul, District of Pedurungan, Semarang. Thesampling technique used in this study support the determination of the sample table (Isac and Michael), thusobtained is 206 samples. The analytical method used descriptive analysis and multiple linear regressionanalysis. The test results obtained simultaneously using the F statistic value of F at 177.251. At the 5% errorlevel with df 1 = 2 and df 2 = 206-2-1 = 15 obtained Ftabel = 3.04 which means that there was a significantinfluence knowledge and attitudes towards adolescent preparedness. The magnitude of the influence of bothcan be seen from the value of the determination coefficient equal to 0.636, which means that changes inpreparedness adolescents aged 15-18 years in the Village Pedurungan Kidul toward flood risk by 63.6%influenced by the knowledge and attitudes of adolescents.